Maternal Instincts
VIII, 171 p.
Keywords: Maternal Instincts brings together seven new essays exploring conflicting visions of motherhood and sexuality in a period during which both terms were undergoing radical change. Representations of both concepts mutated to accommodate different cultural contexts and individual ideologies. Drawing upon sources including literature, film, medical handbooks, popular science, and legal records, the articles collected here construct a vision of motherhood as alternately idealized, discredited, and fragmented by virtue of its connection with sexualities licit and illicit.